Corporate dividend policies during the COVID-19 pandemic - Nasir Ali; Muhammad Zia-ur-Rehman; Badar Nadeem Ashraf; Falik Shear (Economies, 2022)
In this paper, we examine the changes in corporate dividend policies during the COVID-19 shock. For empirical analysis, we employ annual data of 360 companies from the Pakistan Stock Exchange over the period 2015-2020. Using descriptive analysis and Logit regression models, we find that firms were more likely to either omit or reduce dividend payments during the pandemic year of 2020 as compared to the trends in pre-COVID-19 years of 2015-2019. Further, firms with higher profitability, asset turnover and size were less likely to opt for dividend omissions. On the contrary, dividend omissions were more likely among firms with higher debt ratios. The findings of this study helps to understand firm dividend policies during crisis periods.
Keywords: 330; COVID-19; dividend policy; logit regression; Pakistan